Development of AI-assisted educational statistics teaching materials for students with disabilities - Rikhel Saputri; Delvia Muharramah (UNION : Jurnal Ilmiah Pendidikan Matematika, 2025)
This research aims to produce valid and practical AI-assisted Educational Statistics teaching materials for disabilities students in higher education. The research method used was Research and Development (R&D) with the ADDIE model approach (Analysis, Design, Development, Implementation, and Evaluation). This study involved 6 disabilities students from UIN Sulthan Thaha Saifuddin Jambi as trial subjects. Data analysis techniques were carried out quantitatively to measure product validity and practicality through expert validation sheets and student response questionnaires. The results showed that the Canva AI-assisted teaching materials developed obtained a very high validity level with an average percentage of 92.75% from media expert validation (96%), material (92%), language (93%), and questionnaire (90%). The Practicality testing yielded a score of 4.06, classified as "practical" based on student responses. The materials integrate text-to-speech features, AI chatbot, statistics calculator, and accessible design enabling independent learning. These findings demonstrate that AI-assisted teaching materials are feasible and effective for facilitating accessible and independent learning in Educational Statistics for students with disabilities in higher education. This research contributes practical AI technology-based inclusive learning solutions and theoretical frameworks for developing adaptive teaching materials in Indonesian higher education.